2017
DOI: 10.1101/218891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADAM17 is the Principal Ectodomain Sheddase of the EGF-Receptor Ligand Amphiregulin

Abstract: The epidermal growth factor (EGF)-receptor ligand amphiregulin (AREG) is a potent growth factor implicated in proliferative skin diseases and in primary and metastatic epithelial cancers. AREG in vitro, synthesized as a pro-peptide, requires conversion to an active peptide by metalloproteases by a process known as ectodomain shedding. Although, (Adam17) a disintegrin and metalloprotease 17 is implicated in ectodomain shedding of AREG, it remains to be established in vivo whether ADAM17 contributes to AREG shed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…More intriguingly, phagocytic activity of macrophages did not influence AREG transcription, in contrast to its prominent effect on AREG secretion, which presents the possibility that MSCs induce AREG transcription and secretion through separate mechanisms and AREG secretion might share the same pathway with phagocytosis in macrophages. Because ADAM17 is the major sheddase involved in activation and release of AREG from the cell membrane (Hosur et al, 2018), we measured the expression of ADAM17 transcript and protein in macrophages, but could not find an increase in macrophage ADAM17 by MSCs. Remarkably, a series of studies have reported that AREG is secreted to a substantial part in the form of EVs and that AREG-containing EVs are highly functional in eliciting EGFR signaling in recipient cells (Higginbotham et al, 2011;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…More intriguingly, phagocytic activity of macrophages did not influence AREG transcription, in contrast to its prominent effect on AREG secretion, which presents the possibility that MSCs induce AREG transcription and secretion through separate mechanisms and AREG secretion might share the same pathway with phagocytosis in macrophages. Because ADAM17 is the major sheddase involved in activation and release of AREG from the cell membrane (Hosur et al, 2018), we measured the expression of ADAM17 transcript and protein in macrophages, but could not find an increase in macrophage ADAM17 by MSCs. Remarkably, a series of studies have reported that AREG is secreted to a substantial part in the form of EVs and that AREG-containing EVs are highly functional in eliciting EGFR signaling in recipient cells (Higginbotham et al, 2011;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 96%